Competing-destinations gravity model: an application to the geographic distribution of FDI - de Mello-Sampayo, F. (Applied Economics, 2009)
The competing-destinations formulation of the gravity model ensues from the fact that unlike the classical version, this approach explicitly acknowledges the interdependence of the flows between a set of alternative locations, i.e. country-recipients are competing for Foreign Direct Investment (FDI). This article examines empirically a range of theoretical hypotheses about the determinants of FDI location in a panel data regression framework. The results of the estimation of a gravity model lend support to the proximity-concentration and internalization hypotheses. Also, the fact that FDI has been found to be decreasing in the competition posed by alternative locations is suggestive of the superiority of the competing-destinations version of the gravity equation over its classical formulation.